Firm networks and firm development: The role of the relational mix - Lechner, Christian; Dowling, Michael; Welpe, Isabell (Journal of Business Venturing, 2006)
This study examines the role of different networks, called the relational mix, on the development of the entrepreneurial firm. Our regression analysis of survey data from 60 venture capital-financed firms questions the importance of network size on firm development. Rather, our results suggest that different types of networks are more important for firm development. In particular, we found a significant positive relationship for reputational networks and a weak significant negative relationship for cooperative technology networks at founding with time-to-break-even. Social networks at founding have no direct effect on time-to-break-even and a significant negative relationship with sales in the years after foundation. Furthermore, our findings show the important role of marketing information and co-opetition networks (relationships with direct competitors) on firm development in the years after foundation. These results suggest that the relational mix is a more appropriate construct for explaining network development than network size alone.